2010
DOI: 10.1542/peds.2009-3352
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Acetaminophen Is Not Associated With Liver Injury in Children: A Systematic Review

Abstract: Hepatoxicity after therapeutic dosing of acetaminophen in children is rarely reported in defined-population studies. Case reports suggest that this phenomenon may occur, but few reports contain sufficient data to support a probable causal relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…Its safety in daily doses not exceeding 90 mg/kg (15 mg/kg every 4 hours) has been extensively supported (Lesko and Mitchell, 1999;Mohler et al, 2000;Muniz et al, 2004). This was validated by the systematic review from Lavonas et al (2010) that included 62 pediatric studies encompassing 32,414 patients receiving therapeutic doses of acetaminophen and found no cases of overt liver injury. In addition, the report of Pershad et al (1991) that described an 18-month-old child who received acetaminophen at a dose of 19.5 mg/kg at 4-hour intervals for 4 days and who subsequently developed hepatorenal failure has emphasized that a schedule exceeding the 90 mg/ kg threshold risks serious liver injury.…”
Section: Discussionmentioning
confidence: 93%
“…Its safety in daily doses not exceeding 90 mg/kg (15 mg/kg every 4 hours) has been extensively supported (Lesko and Mitchell, 1999;Mohler et al, 2000;Muniz et al, 2004). This was validated by the systematic review from Lavonas et al (2010) that included 62 pediatric studies encompassing 32,414 patients receiving therapeutic doses of acetaminophen and found no cases of overt liver injury. In addition, the report of Pershad et al (1991) that described an 18-month-old child who received acetaminophen at a dose of 19.5 mg/kg at 4-hour intervals for 4 days and who subsequently developed hepatorenal failure has emphasized that a schedule exceeding the 90 mg/ kg threshold risks serious liver injury.…”
Section: Discussionmentioning
confidence: 93%
“…While the elevations observed in this study were minimal, it is possible that acetaminophen-induced ALT elevations could progress to clinical liver injury if potentiated by other factors such as CYP 2E1 induction, malnutrition or oxidative stress. However, analysis of prospective trials that treated adult or pediatric patients with the therapeutic doses for a variety of medical conditions found no cases of acute liver failure [1,21]. …”
Section: Discussionmentioning
confidence: 99%
“…All of the deaths and all but 6 cases of hepatic abnormalities involved doses of paracetamol greater than 75 mg/kg/day. Another recent systematic reviews reported no cases of hepatic injury among 32,414 children who received adequate therapeutic doses of paracetamol, and those studies showed that there are very few cases of children who develop hepatic abnormalities when given repeated doses of paracetamol 5,6 .…”
Section: Epidemiologymentioning
confidence: 98%
“…Accumulation of the toxic metabolite can then exert untoward effect of oxidative stress with mitochondrial dysfunction, cytokines and chemokines disbalance which leads to cell death alterations in hepatic blood flow, inflammation, and liver necrosis 7 . Children younger than six years of age appear to be less susceptible to hepatotoxicity due to greater capacity for conjugation with sulfate and increased supply and regeneration of glutathione 6 , with adult patterns of metabolism are reached between 10 and 12 years of age. Pathophysiology of liver damage is important for understanding significance and pivotal role of acetylcysteine (also known as N-acetylcysteine) as primary therapeutic option.…”
Section: Pathophysiologymentioning
confidence: 99%